知识经济与中国知识产业 = Knowledge economy and China's knowledge industry - 饶健 Rao, Jian (2008)
Since 1990's, the science and technology of human being has been developing dramatically . The world has entered the era of Knowledge Economy. A country's level of development in Knowledge Industry reflects her development situation in Knowledge Economy. But the development of Knowledge Industry are uneven in the world . In order to measure the gap between China and developed countries in Knowledge Industry ,the thesis compare their Knowledge Industry indepth , and tries to find out the problems and strategies facing Chinese Knowledge Industry. Through the comparison and analysis, the thesis finds out large gap existing between China and developed countries in the Knowledge Industry .particularly in IT -. Education and R&D High Technology.